Obtaining Naturalness of Cultural Words Translation Procedures in the Novel Assassin’s Creed: Revelations by Oliver Bowden - Mutiara Fisabella; Jepri Jepri; Adi Prautomo (Prologue: Journal on Language and Literature, 2022)
This research aims to determine the applied translation procedures in the cultural words translation and the naturalness of cultural words translations obtained by the applied procedures found in Oliver Bowden's Assassin's Creed: Revelations novel. Newmark’s theory of translation procedures is used to determine the types of translation procedures, whereas Nida and Taber’s formal and dynamic equivalence theory is used to determine which procedure produced natural cultural words translation. The method used in this research is the qualitative-descriptive method. The research data were collected from the dialogues and narrations found in the selected novel and its translation. Based on the analysis, the research yielded two results. First, the translation procedures applied in the cultural words translations are cultural equivalent, couplets, synonymy, naturalization, notes, descriptive equivalent, transference, shifts or transpositions, recognized translation, functional equivalent, and modulation. Second, only 9 out of 11 procedures successfully obtained naturalness of cultural words translation. The procedure producing the most natural cultural words translations is the cultural equivalent procedure as the cultural words translations it produced are oriented toward dynamic equivalence. On the other hand, the procedure with the least natural cultural words translation is the transference procedure due to the it producing exclusively formal equivalence-oriented translations.